Effects of LED exposure on the sensory properties of soybean oil. Issue 9 (20th August 2022) - Zhou, Peiyuan; Lawrence, Peter; Abbaspourad, Alireza; Dando, Robin
Abstract : Abstract: Soybean oil is an important commodity in the US and abroad. As lipids are vulnerable to oxidation, damage to soybean oil has been previously reported to arise from prolonged light exposure. Here, we assessed the extent of damage to samples of soybean oil from light, tested with sensory evaluation, assaying the effects of both LED and fluorescent lighting (both at 2000 lux) exposure to oil in PET bottles, using a variety of sensory approaches. Threshold testing ( n  = 66) suggested that differences in the sensory properties of soybean oil could be detected by a human panelist after only 32 h of LED exposure. Sensory flash profiling ( n  = 21) again confirmed that light‐exposed samples were perceived differently to shielded samples, with LED‐exposed samples clustering together, but separately from those instead exposed to fluorescent light. These differences did not necessarily result in a drop in liking of the samples, assessed with consumer testing ( n  = 94), despite a trend for lower liking in exposed versus shielded samples. With similar levels of light exposure, elevated dissolved oxygen levels could be mitigated with O2 scavenging. Our results suggest that soybean oil may be reaching the consumer at a differing quality than intended, which may be mitigated with superior packaging technologies. Practical Application: Soybean oil is used widely in the US and global food systems; however, it can be damaged via light oxidation. Here, we show that human panelists can readily detect the sensory signals from light damage in oil exposed for only short periods of time, via either fluorescent or LED light sources. The results suggest that superior soybean oil could be delivered to the market if improvements in packaging technologies were considered.